Validation of the rainfall-runoff SCS-CN model in a catchment with limited measured data in Zimbabwe - Nhamo, Luxon; Chilonda, Pius (Academic Journals, 2013)
An evaluation of available opportunities to revive irrigation on a long abandoned irrigation scheme in a dry region of Zimbabwe is presented by assessing water availability at catchment level. The aim is to enhance the livelihoods, income and nutrition of the communities that depend on the irrigation scheme through a sustainable management of revitalised irrigation infrastructure and ensure food security. Runoff generated in the catchment, with potential to flow into the dam that supplies water to the scheme, is estimated using the Soil Conservation Service curve number (SCS-CN) model. The model simulates runoff at catchment level using daily rainfall data. An overview of the methodology and the various steps followed are provided. Daily rainfall and dam water levels are the only measured data available for the catchment. The dam water levels are used to determine the dam water volumes using rating tables. The dam water volumes are used to calculate the daily water inflows into the dam and these are compared with simulated water discharge rates obtained from the model. The plotted hydrographs of both simulated and measured values coincided very well in shape with great precision validating the SCS-CN model for simulating runoff in ungauged catchments.